Luminescent amphiphilic nanogels by terpyridine-Zn(II) complexation of polymeric micelles. (December 2020) - Abu Saleh, D.; Rana, U.; Higuchi, M.; Sosnik, A.
Abstract: In this work, we investigated terpyridine (tpy)/Zn(II) complexation for the crosslinking of polymeric micelles of the branched poly(ethylene oxide)–poly(propylene oxide) block copolymer Tetronic® 1107 (T1107) in water and produce physically stable amphiphilic luminescent nanogels. Nanoparticles displayed a size of 235 ± 25 and 318 ± 57 nm before and after Zn(II) crosslinking, respectively, as measured by dynamic light scattering. High-resolution scanning electron microscopy analysis revealed the multimicellar nature of the crosslinked nanoparticles. In addition, Zn(II) complexation prevented nanoparticle disassembly after extreme dilution below the critical micellar concentration and reduced the minimum concentration required for the reverse thermal gelation of concentrated aqueous T1107 systems. The cell compatibility and uptake were initially assessed in the murine macrophage cell line RAW 264.7. Results showed that complexation increases the cell compatibility of the nanoparticles with respect to the non-complexed counterparts. In addition, non-crosslinked nanoparticles accumulated in the cell membrane, while the complexed ones were internalized, as observed by confocal laser scanning fluorescence microscopy. Then, the antiproliferative activity of the crosslinked nanoparticles was confirmed in the rhabdomyosarcoma cell line Rh30; their inhibitory concentration 50 (IC50 ) being 101 μg/mL (6.7 μM). Finally, the encapsulation and release of the hydrophobic antiretroviral efavirenz was characterized in vitro. Complexation slightly reduced the release kinetics with respect to the pristine nanoparticles. Overall results demonstrate the promise of this simple modification strategy to produce amphiphilic nanogels with a set of advantageous physicochemical, optical, and biological properties. Graphical abstract: Image 1 Highlights: PEO–PPO polymeric micelles were crosslinked by terpyridine (tpy)/Zn(II) complexation to produce luminescent nanogels. Zn(II) complexation stabilized the nanoparticles on dilution and reduced the minimum concentration required for gelation. Crosslinked nanoparticles can be tracked inside cells and display antiproliferative activity against cancer cells in vitro.